Isolation and screening of a chitin deacetylase producing Bacillus cereus and its potential for chitosan preparation - Zhang, Yingying; Luo, Xi; Yin, Longfei; Yin, Fengwei; Zheng, Weilong; Fu, Yongqian (Frontiers in Bioengineering and Biotechnology, 2023)
Chitosan is a biopolymer material extracted from marine biomass waste such as shrimp and crab shells, which has good biocompatibility and degradability with great potential for application in the field of wastewater treatment and soil remediation. The higher the degree of deacetylation (DD), the better the adsorption performance of chitosan. Chitin deacetylase (CDA) can specifically catalyze the deacetylate of chitin in a green reaction that is environmentally friendly. However, the scarcity of high yielding CDA strains has been regarded as the technical bottleneck of chitosan green production. Here, we screened a natural chitin degrading bacterium from coastal mud and identified it as Bacillus cereus ZWT-08 by re-screening the CDA activity and DD values. By optimizing the medium conditions and enzyme production process, ZWT-08 was cultured in fermentation medium with 1% (m/V) glucose and yeast extract at pH 6.0, 37 ̊C, and a stirring speed of 180 r/min. After fermenting in 5L fermenter for 48 h, the deacetylation activity of the supernatant reached 613.25 U/mL. Electron microscopic examination of the chitin substrate in the fermentation medium revealed a marshmallow-like fluffy texture on its structural surface. Meanwhile, 89.29% of the acetyl groups in this chitin substrate were removed by enzymatic digestion of CDA produced by ZWT-08, resulting in the preparation of chitosan a DD higher than 90%. As an effective strain for chitosan production, Bacillus cereus ZWT-08 plays a positive role in the bioconversion of chitin and the upgrading of the chitosan industry.